Factors affecting customer purchase intention towards halal foods - Nor Arina Mastura, Che Omar (2020)
The main objective of this research is to examine the factor affecting customer purchase intention towards Halal food in Malaysia especially by University students. The research investigates on three factors that affect the purchase intention towards Halal food in Malaysia which are Halal knowledge, Halal logo and attitude. Data were collected from 302 students in Universiti Malaysia Perlis. The internal consistency reliability test of Cronbach‘s Alpha indicated that all scale items were proven reliable. Correlation and Multiple Regression were used to examine the relationship between independent variable and dependent variable. The result showed that are positive relationship between two factors which is Halal logo and attitude. Halal knowledge and purchase intention shows the negative relationship. The result also showed the attitude is the most important factor affecting customer purchase intention towards Halal food in Malaysia.